Blockchain Letter Of Credit: A Systematic Literature Review - Ruslan, Zuhri (Fakultas Ekonomi Universitas Gresik, 2022)
Letter of Credit, a vital international trade instrument, painfully relies on paper and exposes to fraud. Blockchain LC, smart contracts, and the Internet of Things may overcome the problem. The research aims to systematically analyse the literature to find how blockchain can disrupt the LC. The method conducted in this research is a Systematic Literature Review. The result of the research is that from 2069 papers, 12 papers were selected to answer the research questions. It was found that blockchain disrupts current LC practices by simplifying and automating the process. Blockchain also significantly reduces the processing time and provides better transaction security. However, it is to be noted that there are factors that impede the adoption of blockchain LC, out of which legal hurdle is the most crucial. It is necessary to have collective willingness from the user and a supportive legal environment so that International trade can benefit from the blockchain LC technology.